2019
DOI: 10.1111/jtxs.12476
|View full text |Cite
|
Sign up to set email alerts
|

The impact of modification techniques on the rheological properties of dysphagia foods and liquids

Abstract: Modifying food and the textures of food has been done for decades within the food science and technology field. More recently, modifying the texture of foods has been used to manage swallowing disabilities (dysphagia). Swallowing disabilities are often associated with dehydration and malnutrition, thus nutritional intervention has formed part of serving texture‐modified diets. The question remains whether these modification techniques are viable for individuals with swallowing disabilities living in majority w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The rheological properties of foods influence their processability, texture, mouthfeel, and shelf life . The main factors affecting the rheological properties of foods were temperature, processing methods, and food ingredients . As the main ingredient of starch‐based foods, it was reported that the granular swelling of starches were significantly related to the rheological properties of starch‐based foods .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rheological properties of foods influence their processability, texture, mouthfeel, and shelf life . The main factors affecting the rheological properties of foods were temperature, processing methods, and food ingredients . As the main ingredient of starch‐based foods, it was reported that the granular swelling of starches were significantly related to the rheological properties of starch‐based foods .…”
Section: Introductionmentioning
confidence: 99%
“…[5] The main factors affecting the rheological properties of foods were temperature, processing methods, and food ingredients. [5,6] As the main ingredient of starch-based foods, it was reported that the granular swelling of starches were significantly related to the rheological properties of starch-based foods. [7][8][9][10] As detailed by Doublier, [8] the degree of swelling determined the friction among the swollen starch granules, which affected their rheological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Food marketing and packaging (Spence, 2016; Cognitive neurosciences Music: (Carvalho et al, 2016;Kantono et al, 2016;Kantano et al, 2018) Background sounds: (Callan, Callan, & Ando, 2018;Lowe, Rigler, & Haws, 2018;Rahne, Köppke, Nehring, Plontke, & Fischer, 2018;Trautmann, Meier-Dinkel, Gertheiss, & Mörlein, 2017) Dysphagia sciences Textural modifications: (Cichero, 2018;Cichero et al, 2017;De Villiers et al, 2019;IDDSI, 2019;Swan et al, 2015) FIGURE 1-A2: The broader study involved three main phases (initial exploration, pilot study and sensibility exploration). Phase 3 formed the primary focus of this article.…”
Section: Competing Interestsmentioning
confidence: 99%
“…Foams are also used to enhance sensory features, such as enhanced texture and flavors of food. More importantly, food foams are used to deliver liquid in a more easy-to-swallow form, especially for dysphagic patients[ 21 ]. For example, the aeration of water or milk into foams changes their texture and improves nutrients delivery to dysphagic patients.…”
Section: Introductionmentioning
confidence: 99%